KETERSEDIAAN DAN KEAKURATAN KONSEP MENDEL DALAM BUKU TEKS BIOLOGI SMA - Kusniawati, Kusniawati; Candramila, Wolly; Wahyuni, Eko Sri (Universitas Tanjungpura, 2025)
Textbooks are one of the factors that cause misconceptions, despite their function as an easily accessible learning resource for students and teachers. This study aims to identify the availability of important concepts in books used by high school biology teachers and identify potential misconceptions in high school class XII Biology textbooks on the topic of Mendelian inheritance patterns and categorise based on Dikmenli, Cardak and Oztas misconception categories. This research uses a qualitative descriptive approach with the type of research used is content analysis. Data collection techniques were conducted by interview and documentation study. Data collection instruments are interview sheets and data analysis sheets. Based on the results of the study, 13 important concepts were obtained in accordance with basic competencies. The availability of concepts in books A and B presents 9 concepts, book C presents 8 concepts and book D presents 6 concepts. The results found 7 out of 13 important concepts showed potential misconceptions in 3 of the 4 books analysed. Book A showed 8 potential misconceptions with 6 categories of misidentifications, 1 oversimplification and 1 overgeneralization. Book B has 3 potential misconceptions with 2 categories of misidentifications and 1 overgeneralization. Book C shows 3 potential misconceptions with misidentification category. These findings emphasise the need for attention to misconceptions in Biology textbooks.